Modern State Development, Capacity, and Institutions - Lambrechts, Derica (African Sun Media, 2017)
This book makes an important original conceptual and theoretical contribution to our understanding of modern state development, the role of the state, and the South African transition to democracy. Its focus on related concepts such as state capacity, political trust and tolerance adds to insights on the dynamics of political and democratic transitions. Furthermore, the selected focus areas as well as the comparative approach add new insights into the peculiarities of the South African transition, state development, state capacity and state institutions. Its focus on societal dynamics and state-society relations is a significant contribution.